Pengaruh Risiko Persepsi, E-Wom Dan Trustmark Terhadap Keputusan Pembelian Online Di E-Commerce Dengan Kepercayaan Sebagai Mediasi - Cahya, Nanang Nur; Hendri, Nedi; Darmayanti, Elmira Febri (Universitas Muhammadiyah Metro, 2022)
This study aims to examine the factors that influence decisions in online purchases in E-commerce. This type of research is quantitative research. The analytical method used in this study is the Partial Least Square (PLS) method using the SmartPLS software version 3.0 and the data analysis technique using the SEM (Structural Equation Modeling) approach. The variables used in this study are perceived risk, Electronic word of mouth (E-WOM), Trustmark, purchasing decisions and trust as mediating variables. The results of this study show that perceived risk has a positive effect on online purchasing decisions, Trustmark has a positive effect on online purchasing decisions, E-WOM has a positive and significant effect on online purchasing decisions, trust cannot mediate the effect of perceived risk on online purchasing decisions, trust can mediate the influence of Trustmarks. on online purchasing decisions but not significant, trust cannot mediate the effect of E-wom on online purchasing decisions. The implications of this research are relevant for the online business sector to pay attention to the factors that influence purchasing decisions